Anatomical and chemical analyses on wooden artifacts from a Samnite sanctuary in Hirpinia (Southern Italy). (May 2015) - Capano, Manuela; Pignatelli, Olivia; Capretti, Chiara; Lazzeri, Simona; Pizzo, Benedetto; Marzaioli, Fabio; Martinelli, Nicoletta; Gennarelli, Ida; Gigli, Stefania; Terrasi, Filippo; Macchioni, Nicola
Abstract: Objects of this study are the wooden artifacts discovered in the archaeological excavation of Mephitis goddess sanctuary in the Ansanto Valley (Rocca San Felice – AV, Southern Italy). At the moment of discovery, in the mid of last century, woods were waterlogged and mineralized, and they were restored to allow their preservation. Purpose of this work was the wood identification, in order to gain information on some technological aspects, and the analysis of wood preservation state. Wood species were identified by means of magnifiers or optical and scanning electron microscopes, while the state of preservation was studied through microscopy and chemical analyses (FTIR-ATR, ash content and pH measurement). Four different taxa have been identified with certainty among all the findings: Quercus sp., Fagus sylvatica L., Rosaceae, Populus/Salix . It was not possible to identify the wood of all the findings, because some sampled fragments were too small or because of the deformation of wood tissues. The state of preservation showed a great variability over the analyzed findings. A general damage degree was observed, sometimes also macroscopically visible. The polarized light microscope and FTIR-ATR spectroscopy demonstrated the absence of cellulose in the analyzed samples. The wood cell wall was not detectable by means of SEM because it is completely covered by restoration material. Because of the lack of visibility, it was impossible to identify the type of biological damage occurred to the wood. Highlights: The wood taxa and the preservation state of archaeological wooden artifacts from Southern Italy were analyzed. The wooden artifacts belong to four taxa, with a deciduous oak predominance. A high mineral permeation degree was discovered in the archaeological materials. Cellulose is disappeared in most of the analysed woods. The carvings show different degradation levels.